2012
DOI: 10.1002/mmce.20637
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic generation and wave mixing in nonlinear metamaterials and photonic crystals (Invited paper)

Abstract: The basic concepts and phenomenology of wave mixing and harmonic generation are reviewed in context of the recent advances in the enhanced nonlinear activity in metamaterials and photonic crystals. The effects of dispersion, field confinement and phase synchronism are illustrated by the examples of the on-purpose designed artificial nonlinear structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 137 publications
(257 reference statements)
0
9
0
Order By: Relevance
“…However, there are sufficient indications that the nonlinear response of metamaterials may significantly differ from that of the constituent materials and the respective equivalent homogenised medium. To understand these discrepancies, the microscopic nonlinear interactions need to be treated in a self-consistent manner [4]- [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are sufficient indications that the nonlinear response of metamaterials may significantly differ from that of the constituent materials and the respective equivalent homogenised medium. To understand these discrepancies, the microscopic nonlinear interactions need to be treated in a self-consistent manner [4]- [6].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies have been concerned with the linear wave phenomena characterized in terms of the effective parameters of homogenised media. The nonlinear effects in metamaterials have attracted an increasing interest lately being primarily driven by the effort to boost nonlinear optical activity, see, e.g., [1] - [4]. Enhanced nonlinear response of metamaterials and photonic crystals has usually been demonstrated by tailoring the linear characteristics such as dispersion and resonant field localisation while nonlinearity itself was described by the phenomenological optical constants of the constituent particles.…”
Section: Introductionmentioning
confidence: 99%
“…Although the nonlinear wave interactions in solids are normally weak, they exhibit unique properties essential for diverse practical applications. For example, it has been shown that metamaterials and photonic crystals with nonlinear inclusions can be instrumental for increasing the efficiency of frequency conversion and harmonic generation in THz and optical ranges [1]- [3]. Since the majority of the currently available metamaterials are fabricated as stacked layers, it is expedient to investigate their nonlinear characteristics in planar layered structures.…”
Section: Introductionmentioning
confidence: 99%
“…Since the majority of the currently available metamaterials are fabricated as stacked layers, it is expedient to investigate their nonlinear characteristics in planar layered structures. The recent works in this area have been primarily concerned with the second and third harmonic generation in such type of artificial structures [3]- [8]. Conversely, processes of nonlinear scattering and frequency mixing in finite layered structures illuminated by two or more plane waves of different tones incident at dissimilar angles and the mechanisms of the resonance frequency conversion and combinatorial frequency generation (CFG) still remain scarcely explored and poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Multilayered media increase the efficiency of nonlinear optical effects via phase matching or local field enhancement (Ref. [14] and references therein). It has been shown that the further inclusion of cubic nonlinearities can improve the quality of subwavelength imaging by inhibiting diffraction via self-focusing while maintaining broadband operation and increased propagation distances compared to linear metamaterials [15].…”
Section: Introductionmentioning
confidence: 99%